Community Participation in Waste Management at Ramli Graha Indah Air Putih Waste Bank - Farhan, Muhammad; Rusdi, Rusdi; Yuliawati, Ratna (Lambung Mangkurat University, 2024)
The issue of waste has become a national concern and a significant topic in urban environmental problems. The worsening state of the environment requires many parties to take an active role in improving current conditions. An example is the Ramli Graha Indah waste bank in the Air Putih village, which aims to reduce the volume of waste. This study aims to determine whether the community participates in waste management at the Ramli Graha Indah waste bank and what motivates them to contribute. A qualitative approach with descriptive techniques was employed, involving in-depth interviews to describe the conditions of the research subjects and objects, as well as analyzing operational concepts, frameworks, and laws related to the problem. The findings reveal that 7 out of the bank's customers were inactive, primarily due to the distance between their homes and the waste bank. The primary motivation for participation was the financial benefit, such as additional income from waste sales. The study concludes that the long distance from home and the habit of waiting for waste to accumulate are key reasons for inactivity among customers.